Analisis Likuiditas, Leverage, dan Aktivitas pada PT. Gudang Garam Tbk - Listyawati, Reni; Erawati, Teguh; Shafira, Maghfirotus; Taufiqurrahman; Nana, Skolastika Clarisa; Bria, Amanda Serli (DAS Institute, 2025)
This study aims to analyze the financial performance of PT Gudang Garam Tbk during the 2019-2023 period through a financial ratio approach, including liquidity ratios, leverage, and activities. The liquidity ratio in the analysis uses the Current Ratio to evaluate the company's ability to meet short-term obligations. The leverage ratio is analyzed using the Debt to Equity Ratio (DER) to assess the level of debt utilization in the company's capital structure. Meanwhile, the activity ratio is analyzed using Turn Asset Turn Over (TATO) to measure the efficiency of assets in generating income. The results of this study show that the average current ratio of 216 reflects good liquidity. The average DER of 49% indicates a sound financial structure, with the lowest leverage ratio in 2020 at 34% and stable in the range of 52%-53% the following year. The average TATO of 1.39 is slightly below the industry standard of 1.40, indicating a fairly good efficiency in the use of assets, where the TATO drops to 1.29. This study provides a comprehensive overview of PT Gudang Garam Tbk's financial condition and its implications for the company's business sustainability amid the challenges of the cigarette industry faced with strict regulations, competition for alternative products, and changing consumer preferences. This result is expected to be a reference for stakeholders in making strategic decisions to increase the company's competitiveness in the future